Cu2+ modulated DNA-templated silver nanoclusters as a turn-on fluorescence probe for the detection of quinolones. Issue 34 (20th August 2018) - Wang, Renjun; Yan, Xiaolu; Sun, Jing; Wang, Xiao; Zhao, Xian-En; Liu, Wei; Zhu, Shuyun
Abstract : In this contribution, DNA-templated silver nanoclusters (DNA-AgNCs) were successfully utilized as novel fluorescent probes for the detection of quinolones for the first time. Abstract : In this contribution, DNA-templated silver nanoclusters (DNA-AgNCs) were successfully utilized as novel fluorescent probes for the detection of quinolones for the first time. The as-prepared DNA-AgNCs exhibited strong emission at 596 nm, which could be quenched by Cu 2+ ions. The addition of quinolones caused restoration of fluorescence intensity of the DNA-AgNCs–Cu 2+ system. This detection protocol exhibited excellent sensitivities for four kinds of quinolones. For instance, the linear ranges were from 20 to 100 nM for nalidixic acid with the limit of detection (LOD) 2.0 nM, from 5 to 120 nM for cinoxacin with the LOD 1.2 nM, from 5 to 100 nM for ciprofloxacin with the LOD 1.0 nM, and from 1 to 60 nM for moxifloxacin with the LOD 96 pM, respectively. Benefiting from high sensitivity, satisfactory recoveries were obtained for trace detection of quinolones in real samples, such as tablets and human urine.